Engagement, flow, self-efficacy, and Eustress of University Students: A cross-national comparison between the Philippines and Argentina - Mesurado, Belén (Animo Repository, 2016)
© 2016 Taylor & Francis Group, LLC. This study examined how self-efficacy, eustress, and flow interact with academic engagement. First, it aimed to test a theoretical model that proposes that self-efficacy and eustress promote both flow and engagement and that, in turn, the state of flow promotes academic engagement in undergraduate student. We hypothesized that the theoretical model would be invariant for two countries: the Philippines and Argentina. Secondly, this research aimed to compare the levels of self-efficacy, eustress, study-flow and academic engagement experiences in students from both countries. One hundred seventy-six Filipinos and 171 Argentinean students participated in the study by completing inventories using the Utrecht Student Engagement Scale (Schaufeli, Martínez, et al., 2002), Optimal Experience Survey (Mesurado, 2008), Self-efficacy Scale (OSullivan, 2011), and Eustress Scale (OSullivan, 2011). Results show that the theoretical model fits the data well in both countries and is invariant across the Philippines and Argentina. Self-efficacy has a positive effect on flow and engagement, whereas eustress has a significant positive relationship with flow but is not directly associated with engagement. However, eustress has an indirect effect, through flow, on student engagement. On the other hand, there are different levels of engagement, flow, self-efficacy, and eustress. Argentinean students scored higher on absorption, dedication, self-efficacy, and flow. Filipino students, meanwhile, scored higher on eustress.